2015
DOI: 10.1097/01.xha.0000470182.71509.1b
|View full text |Cite
|
Sign up to set email alerts
|

Sexual desire in a sample of married Egyptian women with polycystic ovarian syndrome

Abstract: PurposeThe aim of this study was to evaluate sexual desire in a sample of married Egyptian women with polycystic ovarian syndrome (PCOS). Patients and methodsThis study was carried out on 85 married Egyptian women with PCOS and 63 normal married women (the control group) recruited from the gynecology and obstetrics clinic in Kasr El-Aini Hospital, Cairo University. Every case was subjected to full medical history, full sexual history, general and local examinations, and investigated for serum levels of luteini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Eight studies used the FSFI (Gateva and Kamenov, 2012;Ercan et al, 2013;Ferraresi et al, 2013b;Benetti-Pinto et al, 2015;Lara et al, 2015;Noroozzadeh et al, 2016;Shafti and Shahbazi, 2016;Diamond et al, 2017). Other studies used different scales: the CSFQ (Stovall et al, 2012), the SQ-F (Zueff et al, 2015), the MFSQ (Mansson et al, 2011), the FSDQ (Elkhiat et al, 2015), the ISS (Drosdzol et al, 2007) and the MSQ (Kowalczyk et al, 2015). Four studies used VAS to assess sexual function and effect of clinical characteristics on sexual function (Elsenbruch et al, 2003;Hahn et al, 2005;Tan et al, 2008;Caruso et al, 2009).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies used the FSFI (Gateva and Kamenov, 2012;Ercan et al, 2013;Ferraresi et al, 2013b;Benetti-Pinto et al, 2015;Lara et al, 2015;Noroozzadeh et al, 2016;Shafti and Shahbazi, 2016;Diamond et al, 2017). Other studies used different scales: the CSFQ (Stovall et al, 2012), the SQ-F (Zueff et al, 2015), the MFSQ (Mansson et al, 2011), the FSDQ (Elkhiat et al, 2015), the ISS (Drosdzol et al, 2007) and the MSQ (Kowalczyk et al, 2015). Four studies used VAS to assess sexual function and effect of clinical characteristics on sexual function (Elsenbruch et al, 2003;Hahn et al, 2005;Tan et al, 2008;Caruso et al, 2009).…”
Section: Search Resultsmentioning
confidence: 99%
“…Another limitation is the diversity between the studies; for example four studies were from Islamic countries, including only married women (Ercan et al, 2013;Elkhiat et al, 2015;Noroozzadeh et al, 2016;Shafti and Shahbazi, 2016). Other studies did not mention relationship status or sexual activity of participants (Gateva and Kamenov, 2012;Stovall et al, 2012;Lara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to shed light on the relationship between androgens and sexual function in women with PCOS. Studies that found higher androgen levels to be related to lower sexual function in women with PCOS reported: a negative association between testosterone levels and sexual desire ( Elkhiat etal. , 2015 ); a negative relationship between free and total testosterone and total FSFI score ( Ercan etal.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies used different scales: the CSFQ ( Stovall et al , 2012 ), the SQ-F ( Zueff et al , 2015 ), the MFSQ ( Karsten et al , 2021 ), the FSDQ ( Elkhiat et al , 2015 ), the ISS ( Drosdzol et al , 2007 ), the MSQ ( Kowalczyk et al , 2015 ), Sexual Satisfaction Scales ( Glowinska et al , 2020 ), and the SSQ ( Kałużna et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%